Postoperative complication rates between crohn’s disease and colorectal cancer patients after ileocolic resections: A comparative study - Boaron, Larissa; Facchin, Luiza; Bau, Mariella; Zacharias, Patricia; Ribeiro, Diogo; Miranda, Eron Fábio; de Barcelos, Ivan Folchini; Ropelato, Renato Vismara; Filho, Álvaro Steckert; de Meira Junior, José Donizeti [UNESP]; Sassaki, Ligia [UNESP]; Saad-Hossne, Rogério [UNESP]; et al. (Thieme, 2017)
Introduction: Ileocolic resection (ICR) is the most common surgical procedure performed forCrohn’s disease (CD). Similarly, right-sided Colorectal cancer (CRC) is treated by the sameoperation. The primary aim of this study was to analyze and compare the frequency andprofile of early postoperative complications of ICR between patients with CD and CRC.Methods: Retrospective and observational study with patients submitted to ICR from twoBrazilian tertiary referral units in colorectal surgery. We included patients with diagno-sis of CD or CRC, treated with ICR, at any stage of follow-up. Variables analyzed: age atsurgery, gender, diagnosis, surgical approach (open or laparoscopy), type of anastomo-sis (hand-sewn/stapled; end-to-end/side-to-side), presence and type of early postoperativecomplications (30 days) and mortality, among others.Results: 109 patients were included, 73 with CD (67%) and 36 with CRC (33%). CD patients wereyounger (42.44 ± 12.73 years vs. 66.14 ± 11.02 years in the CRC groups, p < 0.0001) and hadmore previous resections (20 ± 27.4 in CD and 0 in CCR, p = 0.001). There were no significantdifferences between the groups in terms of overall early postoperative complications [17/73(23.3%) in the CD and 5/36 (13.9%) in the CRC groups (p = 0.250)]. There was no significantdifference between the groups in relation to anastomotic leakage (p = 0.185), surgical siteinfections (p = 0.883), other complications (0.829) and deaths (p = 0.069). Conclusions: There was no significant difference in early postoperative complications in patients with CD or CRC submitted to ICR.
Complicações pós-operatórias após ressecções ileocólicas na doença de Crohn e no câncer colorretal: Um estudo comparativo
Keywords: Colorectal cancer; Complication; Crohn’s disease; Postoperative